Pro-angiogenic and osteogenic composite scaffolds of fibrin, alginate and calcium phosphate for bone tissue engineering - Kohli, Nupur (J Tissue Eng, 2021)
Due to the limitations of bone autografts, we aimed to develop new composite biomaterials with pro-angiogenic and osteogenic properties to be used as scaffolds in bone tissue engineering applications. We used a porous, cross-linked and slowly biodegradable fibrin/alginate scaffold originally developed in our laboratory for wound healing, throughout which deposits of calcium phosphate (CaP) were evenly incorporated using an established biomimetic method. Material characterisation revealed the porous nature and confirmed the deposition of CaP precursor phases throughout the scaffolds. MC3T3-E1 cells adhered to the scaffolds, proliferated, migrated and differentiated down the osteogenic pathway during the culture period. Chick chorioallantoic membrane (CAM) assay results showed that the scaffolds were pro-angiogenic and biocompatible. The work presented here gave useful insights into the potential of these pro-angiogenic and osteogenic scaffolds for bone tissue engineering and merits further research in a pre-clinical model prior to its clinical translation.